2005
DOI: 10.1007/s11013-005-7423-2
|View full text |Cite
|
Sign up to set email alerts
|

“Bioethics in Action” and Human Population Genetics Research

Abstract: Recent disputes about human population genetics research have been provoked by the field's political vulnerability (the historic imbalance of power between the geneticists and the people they study) and conceptual vulnerability (the mismatch between scientific and popular understandings of the genetic basis of collective identity). The small, isolated groups often studied by this science are now mobilizing themselves as political subjects, pressing sovereignty claims, and demanding control over the direction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…Most of the earliest genomic scans for adaptation 5,1319 focused on population samples from phases I and II of the , including Yoruba individuals living in Ibadan, Nigeria; Han Chinese individuals living in Beijing, China; Japanese individuals living in Tokyo, Japan; individuals with European ancestry living in Utah, United States; and/or Perlegen population samples (African American, Asian American and European American). This work has been complemented by more recent studies that have included genomic scans for adaptation in the Human Genome Diversity Project (HGDP), which includes 51 worldwide population samples 11,12,2022 .…”
Section: Identifying Signatures Of Selectionmentioning
confidence: 99%
“…Most of the earliest genomic scans for adaptation 5,1319 focused on population samples from phases I and II of the , including Yoruba individuals living in Ibadan, Nigeria; Han Chinese individuals living in Beijing, China; Japanese individuals living in Tokyo, Japan; individuals with European ancestry living in Utah, United States; and/or Perlegen population samples (African American, Asian American and European American). This work has been complemented by more recent studies that have included genomic scans for adaptation in the Human Genome Diversity Project (HGDP), which includes 51 worldwide population samples 11,12,2022 .…”
Section: Identifying Signatures Of Selectionmentioning
confidence: 99%
“…Research into and knowledge about genetic history may be welcomed or rejected, and/or adopted for particular identity-political purposes (Parfitt and Egorova, 1996;Brodwin, 2005). In Alondra Nelson's (2008) study on African American customers of genetic ancestry tracing services, individuals showed some flexibility in the appropriation of the genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Bioethics is no longer viewed simply as a set of abstract principles and guidelines implemented to reproduce the legitimacy and authority of medical professionals (Kleinman, 1996(Kleinman, , 1999Rosenberg, 1999;Timmermans and Berg, 2003). In examining the relation between personal experience and formalised ethics, authors have demonstrated the various ways in which bioethics influences and is played out in vis-à-vis specific economic, political, and medic-scientific scenarios (Petryna, 2002(Petryna, , 2005(Petryna, , 2009Brodwin, 2005Brodwin, , 2008Brodwin, , 2012Jasanoff, 2005;Stark, 2010). Ethical regulation varies between local contexts in relation to specific economic and political circumstances, while ethical deliberation often takes on the characteristics and concerns of the (nation) State in which it is taking place (Jasanoff, 2005;Petryna, 2005Petryna, , 2009Sperling, 2007).…”
Section: Coproduction Imaginaries and (Bio)ethicsmentioning
confidence: 99%